Synchronic and Diachronic Aspects of Kanashi - Saxena, Anju (Trends in Linguistics. Documentation [TiLDOC], 2022)
Kanashi is a Sino-Tibetan language belonging to the West Himalayish subbranch of this language family. It is spoken by fewer than 2,000 individuals in one single village (Malana in Kullu district, Himachal Pradesh state, India). The book presents an overview of synchronic and diachronic aspects of Kanashi: its sound system, its grammar in outline, its intriguing numeral systems, and word lists (English-Kanashi, Kanashi-English).